Meningkatkan Kesabaran Pada Anak Usia Dini Melalui Metode Bcm (Bermain, Cerita, Dan Menyanyi ) di PAUD Permata Bunda Kecamatan Warungkondang - Tia Setiawati (PT. Alahyan Publisher Sukabumi, 2025)
The background of this study is that 11 of the 15 children in Group B at Permata Bunda Preschool have not yet developed patience. An educator must have the desire and ability to teach their students to be good children and be able to change bad traits into good ones. Therefore, the purpose of this study is to increase patience in children at Permata Bunda Preschool. The learning method used to increase children's patience is the Play, Story, and Singing method. Through the Play, Story, and Singing method, the researcher used a Classroom Action Research design, with two cycles of action. The level of children's patience in the initial observation was only 49.25%. Then, actions were taken in cycle I, and the children's patience increased to 64.25%. However, this value did not reach optimal results, therefore, actions were carried out again in cycle II to improve patience. In this study, the researcher used the Classroom Action Research method through two cycles. The results of activities in cycle II showed optimal results of 92%. The results obtained after the second cycle of action indicate that the application of the Play, Story, and Singing method to foster patience in children at Permata Bunda Preschool (PAUD) resulted in optimal improvement and can be reused by teachers as a learning method in the future.